The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/aqc.3668
|View full text |Cite
|
Sign up to set email alerts
|

Assessing common bottlenose dolphin (Tursiops truncatus) population structure in Mississippi Sound and coastal waters of the north central Gulf of Mexico

Abstract: Population structure of highly mobile marine organisms can be complex and difficult to study, but it is important to understand how populations partition themselves within their environment for accurate assessment of both natural and anthropogenic impacts and successful management. The 2010 Deepwater Horizon oil spill negatively impacted common bottlenose dolphins (Tursiops truncatus) within Mississippi Sound and the surrounding north central Gulf of Mexico (GOMx); however, little was known about their underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…Spatial segregation often occurs in socially or genetically structured groups of bottlenose dolphins [ 91 ]. Spatial segregation in common and Indo-Pacific bottlenose dolphins has been identified within estuarine systems, embayments, or lagoons [e.g., 7 , 11 , 12 , 82 , 87 , 91 , 93 , 97 100 ], between or among estuarine and coastal groups [e.g., 8 , 14 , 84 , 99 104 ], as well as in coastal open-water areas [ 9 , 94 , 104 ]. The spatial segregation often reflects site fidelity and occurs despite the lack of physical barriers to movements [e.g., 7 , 88 , 94 , 100 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spatial segregation often occurs in socially or genetically structured groups of bottlenose dolphins [ 91 ]. Spatial segregation in common and Indo-Pacific bottlenose dolphins has been identified within estuarine systems, embayments, or lagoons [e.g., 7 , 11 , 12 , 82 , 87 , 91 , 93 , 97 100 ], between or among estuarine and coastal groups [e.g., 8 , 14 , 84 , 99 104 ], as well as in coastal open-water areas [ 9 , 94 , 104 ]. The spatial segregation often reflects site fidelity and occurs despite the lack of physical barriers to movements [e.g., 7 , 88 , 94 , 100 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Population structure of highly mobile marine organisms can be complex and difficult to study, but it is important to understand how individuals within a population partition their environment, in order to better address conservation challenges (Vollmer et al, 2021). In this regard, recent advancements in the implementation of standardized site fidelity indexes (Tschopp et al, 2018) and considerations on residency patterns when studying cetacean population dynamics (e.g., Zanardo et al, 2016;Hunt et al, 2017;Passadore et al, 2017;Schleimer et al, 2019;Carlucci et al, 2020;Haughey et al, 2020) provide improved methodological tools for dealing with heterogeneity in capture or survival probabilities inherent to the dynamics of social species with fission-fusion societies such as bottlenose dolphins (Connor et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, using photo‐ID data, Mazzoil et al (2008) identified three communities of dolphins within the Indian River Lagoon of Florida, but only two genetic clusters were differentiated by Richards et al (2013) using microsatellite data. Furthermore, analysis of telemetry and photo‐ID data of dolphins inhabiting Mississippi Sound, Mississippi/Alabama in the northern Gulf of Mexico (Mullin et al, 2017) identified at least two social groups but microsatellite data supported only a single population (Vollmer et al, 2021). The fission–fusion nature of dolphin societies might also explain why more social than genetic groups were found in the Barataria Basin.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were genotyped at 43 nuclear polymorphic microsatellite loci previously optimized for T. truncatus (Rosel, Hansen & Hohn, 2009; Rosel et al, 2017; Vollmer et al, 2021; see Table S1). Modifications to original primer sequences were made for D08, DlrFCB12, EV94 and MK8 (Rosel et al, 2017; Vollmer & Rosel, 2017; Vollmer et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation